Produksi Kopi Pro Sebagai Kopi Sehat Dengan Penambahan Bacillus cereus SN7 - Feliatra, Feliatra; Batubara, Ummi Mardhiah; Nursyirwani, Nursyirwani; Lazuardi, Lazuardi; Zevira, Bella Permata; Gustina, Julia; Alfarisy, M. Phyto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Pro coffee is one of the coffee drinks enriched with B.cereus bacterial consortium. Bacillus cereus is a single cell protein that is rich in protein. This program aims to develop student entrepreneurship activities by implementing the results of previous research, namely utilizing probiotic bacteria for healthy coffee entrepreneurship with the addition of probiotic bacteria from seawater. The method used for this program is to provide lectures and practices on pro-coffee processing to students involved in this service. This service activity was carried out in four stages, namely: Training and Competency Improvement Training and competency improvement activities are carried out as an effort to increase the knowledge and competence of Partners and students in processing Pro coffee. The results of the service show that students are able to improve: 1) Knowledge of making probiotic bacteria development media so that it is suitable for human consumption; 2) Making probiotic starter (Bacillus cereus SN7); 3) Making pro coffee; 4) Packaging of pro coffee; and 5) Marketing of pro coffee products